Behavior of Concentrically Loaded RPC Circular Columns Reinforced Longitudinally and Transversally with GFRP Bars - Kadhim, Mohamed Qassim; Hassan, Hassan Falah (Journal of Engineering and Sustainable Development, 2026)
Although reinforced concrete (RC) members with glass fiber reinforced polymer (GFRP) bars have been widely investigated, the axial performance of reactive powder concrete (RPC) columns reinforced with GFRP has not been sufficiently addressed. To fill this gap, an experimental program was carried out on eleven circular specimens, each 150 mm in diameter and 1000 mm in height. The specimens were divided into four groups: three groups of fully GFRP-reinforced columns with hoop spacings of 40, 60, and 80 mm, and a reference group including one steel-reinforced column and one hybrid column combining steel and GFRP bars. Both reference specimens used GFRP hoops at 60 mm spacing. The study examined failure mechanisms, ultimate axial strength, deformation responses (strain and displacement), and ductility. Increasing the main reinforcement ratio from 1.77% to 3.55% enhanced axial capacity by about 46%, while raising the transverse reinforcement ratio from 1.24% to 2.48% improved load capacity by 10–19%. Higher confinement also contributed to better ductility. Although GFRP-RPC columns showed lower nominal strength compared with steel- and hybrid-reinforced RPC columns, their overall structural behavior followed similar trends. The experimental results were further used to evaluate the accuracy of existing design equations in predicting the nominal axial capacity of GFRP-RPC columns.